PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN MAKE A MATCH - suhartati suhartati (Jurnal Lingkar Mutu Pendidikan, 2023)
The aim of this research is to improve social studies learning outcomes through the Make a Match learning model for class VI students at SD Negeri Bleber 1 for the 2022/2023 academic year. Research subjects, sixth grade students at SD Negeri Bleber 1 with addresses at Karanggede, Sumberharjo, Prambanan, Sleman, D.I. Yogyakarta. The type of research is Classroom Action Research for two cycles. Data collection instruments used observation sheets and written tests. The data analysis technique uses descriptive qualitative. The research results are seen from the percentage of learning implementation, social studies learning outcomes, and learning completion. The percentage of learning implementation by cycle I teachers was 71.4% with the criteria "Good". Cycle II increased to 91.1% with "Very Good" criteria. The social studies learning results when pretesting the class average was 55. In the first cycle the class average increased to 74.3. In cycle II, the class average increased to 80. The results of pre-test learning completion were 9 students (30%). Cycle I, the number of students who completed increased from 17 students (40%) to 21 students (70%). Cycle II, the number of students who completed increased by 4 students (13%) to 25 (83%). Based on the research results, it can be concluded that implementing Make a Match learning can improve social studies learning outcomes for class VI students at Bleber 1 Elementary School for the 2022/2023 academic year.